Service quality and customer satisfaction: a study on private hospital in Kuching / Lilyanti Haron - Haron, Lilyanti (2012)
Nowadays, the ownership of health care organizations is changing. Profit- oriented services, ranging from public limited companies to co-operatives or associations, are entering the industry, bringing increasing supply and more power of choices to customers. Simultaneously, people are concerned about health issues and customers (patients, their relatives and citizens) demand more sophisticated services. As a consequence ofthese changes in consumer attitudes towards health, the industry has become more attractive to the private sector. Such growth means that customers are increasingly able to choose among health providers, particularly based on the balance between expectations and experiences. A different approach to health services can now be found in both private and public hospital such as the provision of single rooms with beds that have orthopedic and ergonomic features, private bedrooms, television and sometimes a space with a second bed for relatives. Additionally, these facilities are far more user-friendly, with special areas for children, air-conditioning, vending machines with food and drinks, security and information staff, information points and newspapers.